Advances in Biomaterials and Technologies for Vascular Embolization. Issue 33 (6th June 2019) - Hu, Jingjie; Albadawi, Hassan; Chong, Brian W.; Deipolyi, Amy R.; Sheth, Rahul A.; Khademhosseini, Ali; Oklu, Rahmi
Abstract: Minimally invasive transcatheter embolization is a common nonsurgical procedure in interventional radiology used for the deliberate occlusion of blood vessels for the treatment of diseased or injured vasculature. A wide variety of embolic agents including metallic coils, calibrated microspheres, and liquids are available for clinical practice. Additionally, advances in biomaterials, such as shape‐memory foams, biodegradable polymers, and in situ gelling solutions have led to the development of novel preclinical embolic agents. The aim here is to provide a comprehensive overview of current and emerging technologies in endovascular embolization with respect to devices, materials, mechanisms, and design guidelines. Limitations and challenges in embolic materials are also discussed to promote advancement in the field. Abstract : Advances in biotechnology and material science have facilitated the development of embolic agents for vascular embolization. Both clinical and preclinical embolic agents, including mechanical occlusion devices, particulates, and liquids, are reviewed. The challenges and future insights in this field are also highlighted. An integrated and multidisciplinary approach may offer opportunities to revolutionize the next generation of embolic agents.